THE EFFECT OF USING MONITORING, QUESTIONING, AND REPREDICTING STRATEGY ON STUDENTS’ READING COMPREHENSION - Dormauli Samosir; Berlin Sibarani (Universitas Negeri Medan, 2014)
This study was aimed at finding out the effect of using Monitoring, Questioning, and Repredicting strategy on students reading comprehension. This study used the experimental design. The population of this study was the eighth grade students of SMP Trisakti 2 Medan. There were sixty students as the sample of the research. This study was conducted with two randomized groups namely experimental and control group. The experimental group was taught by using Monitoring, Questioning and Repredicting Strategy while control group was taught without using Monitoring, Questioning, and Repredicting Strategy. The instrument of collecting the data was multiple choice test which consists of 20 items. To obtain the reliability of the test, the researcher used Kuder-Richardson (KR-20) formula. The calculation shows that reliability was 0.70 (high). The data were analyzed by using t-test. The calculation shows that t-observed (5.12) is higher than t-table (2.00) at the level of significance (α) 0.05 with the degree of freedom (df) 58. Therefore, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that teaching reading comprehension by using Monitoring, Questioning, and Repredicting strategy significantly affect reading comprehension.